The role of ATP-sensitive potassium channels in cellular function and protection in the cardiovascular system - Tinker, Andrew (Blackwell Publishing Ltd, 2014)
ATP-sensitive potassium channels (K(ATP)) are widely distributed and present in a number of tissues including muscle, pancreatic beta cells and the brain. Their activity is regulated by adenine nucleotides, characteristically being activated by falling ATP and rising ADP levels. Thus, they link cellular metabolism with membrane excitability. Recent studies using genetically modified mice and genomic studies in patients have implicated K(ATP) channels in a number of physiological and pathological processes. In this review, we focus on their role in cellular function and protection particularly in the cardiovascular system.